PENGARUH KOMUNIKASI PROMOTOR KONSER TERHADAP SIKAP PENONTON (Survei kepada Penggemar NCT 127 yang Menghadiri Konser pada 4 November 2022) - Naomi Zefanya Sumendap, (2023)
As one of the largely orchestrated show to channel fans' liking towards their favorite artists and/or musicians, concerts are now evaluated based on the promotors that held them, which in this research focused more on the chaos ensued in NCT 127's concert in Indonesia, that said to affect audience's will to watch a concert. This research is conducted on a purpose to measure how impactful the influence of the concert promotor towards concert audience based on a survey with NCT 127 fans called NCTzen that uses Instrumental Theory of Persuasion theory as the standard of the research. The method used on this research is quantitative causal-comparative in which utilize primary and secondary source of data. The sampling technique uses purposive sampling that utilizes closed questionnaire based on likert scale with data analysing inferensial technique which includes correlation test, regression test, coefficient of determination test, and hypothesis test. The result of this research reveals that there is a significant and positive impact caused by the influence of the concert promotor towards concert audience in which resulted in the degree of correlation test enters the strong category, so it could be concluded that there is an influence from the concert promotor that affects the concert attendees.